Frequency of maternal stress and psychic risk in newborns who have been hospitalized in a neonatal intensive care unit - Lívia dos Santos Paula; Adriane Celli; Rosa Maria Marini Mariotto; Hellen Nataly Correa Lagos-Guimarães; Andriéllen Marciniak (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: describe the frequency of maternal stress and psychic risk indicators in newborns who were exposed to the neonatal intensive care unit (NICU) after hospital discharge. Methods: observational, analytical, cohort study, sample of 26 participants (13 exposed and 13 not exposed to the NICU). Maternal stress was assessed by Inventário de Sintomas de Stress para Adultos de Lipp (ISSL) (Lipp's Stress Symptoms Inventory for Adults) and psychological risk by Indicadores Clínicos de Risco para o Desenvolvimento Infantil (IRDI) (Clinical Risk Indicators for Child Development), 15 days after hospital discharge and at 4 months of corrected age. Results: the study found a frequency of stress of 23.1% in mothers of newborns who were exposed to NICUs and 38.5% of psychological risk in these newborns. The following associations were found: maternal stress and newborn exposure to the NICU (p=0.037); maternal stress and newborn exposure time to NICU (p=0.031); psychological risk and prematurity (p=0.014). There were no association between psychic risk and maternal stress; and there was no diference in the frequency of psychological risk between the groups of newborns. Conclusions: newborn hospitalization in the NICU is associated with maternal stress, but not with psychological risk. Prematurity can cause psychological risk. Maternal stress was not associated with psychological risk.